A Survey Of Health Education And First Aid Practices In Basic Schools In Three Regional Capitals In Ghana - Owusu-Addo, Augustine (Advances in Social Sciences Research Journal, 2019)
The research was conducted to unravel the health education offered at the basic schools and the first aid services rendered for the pupils. It was conducted in some enlightened municipalities in the middle belt of Ghana. Cross-sectional descriptive design was employed to guide the conduct of the research. Head teachers and classroom teachers provided data to address the research problem. The research unveiled that the pupils in the schools enjoy health education programmes covering varied health issues albeit inadequate. The research also revealed that first aid is provided for pupils in the schools to cater for minor health conditions, reduce pains and sustain victims till experts come in. The staff however encountered various challenges in performing both health education and first aid services in the schools. It is then essential for educational authorities in the regions to rekindle and re-double their efforts in resourcing basic schools, their head teachers and the teachers empower to deliver these services in the schools.